2000
DOI: 10.1161/01.cir.101.19.2264
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Extracellular Superoxide Dismutase Activity in Patients With Coronary Artery Disease

Abstract: In patients with CAD, vascular EC-SOD activity is substantially reduced. The close relation between endothelium-bound EC-SOD activity and FDD suggests that reduced EC-SOD activity contributes to endothelial dysfunction in patients with CAD. In young hypercholesterolemic individuals, however, endothelium-bound EC-SOD activity is increased and may, in part, counteract impairment of endothelial function as the result of increased formation of oxygen free radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
136
0
9

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(156 citation statements)
references
References 40 publications
11
136
0
9
Order By: Relevance
“…34 EC-SOD is anchored to heparan sulfate proteoglycans on endothelial cells and released by treatment with heparin in vitro and in vivo. Landmesser et al 35 reported that heparin-releasable (that is, endothelium-bound) EC-SOD activity was substantially reduced in patients Olmesartan improves endothelial function S Takiguchi et al with coronary artery disease, as well as a close relationship between endothelium-bound EC-SOD activity and endothelial function. They also demonstrated that ACEI and ARB improved endothelial function in the radial artery by increasing endothelium-bound EC-SOD activity.…”
Section: Discussionmentioning
confidence: 99%
“…34 EC-SOD is anchored to heparan sulfate proteoglycans on endothelial cells and released by treatment with heparin in vitro and in vivo. Landmesser et al 35 reported that heparin-releasable (that is, endothelium-bound) EC-SOD activity was substantially reduced in patients Olmesartan improves endothelial function S Takiguchi et al with coronary artery disease, as well as a close relationship between endothelium-bound EC-SOD activity and endothelial function. They also demonstrated that ACEI and ARB improved endothelial function in the radial artery by increasing endothelium-bound EC-SOD activity.…”
Section: Discussionmentioning
confidence: 99%
“…18,35 Vascular Ec-SOD activity correlated with the endothelium dependent vasodilatation and is low in patients with a history of myocardial infarction and coronary artery disease. 6 Restoration of Ec-SOD availability is associated with improvement of endothelial function in patients with CAD and is related to reduction of oxidative stress in vessel wall. 5 Earlier studies carried out in rats have shown that infusion of recombinant Ec-SOD protein resulted in reduced levels of creatine kinase in the left ventricular free wall and SOD bound to endothelial surface was also associated with lower cardiac damage in Langendorffperfused rat hearts subject to 15 min of global ischemia followed by reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…4 A number of recent clinical studies have reported reduced levels of human extracellular superoxide dismutase (Ec-SOD) in patients with coronary artery disease and myocardial infarction. [5][6][7] Superoxide anion is product of oxygen metabolism and is produced by activated inflammatory cells. [8][9][10] SODs are family of metalloproteins that scavenges superoxide anion radicals and form oxygen and hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in Apo (E)-deficient mice, we have previously found that the vascular smooth muscle cell expression of ecSOD declines as the severity of atherosclerosis increases (15). Landmesser et al have recently shown that plasma levels of ecSOD are markedly reduced in individuals with advanced atherosclerosis (51). One explanation for these findings is that atherosclerosis is associated with a loss of endothelium-derived NO production and/or bioreactivity, leading to a decrease in ecSOD expression.…”
Section: Figurementioning
confidence: 92%